Is low amniotic fluid index an indicator of fetal distress and hence delivery? - Pai, Meghna M.; Pai, Muralidhar V.; P. S., Roopa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Amniotic fluid Index (AFI) is an indicator of fetal well-being. Low AFI is considered to be one of the indications for delivery as it may be associated with fetal distress and birth asphyxia. We sought to determine whether low AFI is an indicator of fetal compromise and an indication to deliver. Methods: This prospective, observational study was conducted at Department of Obstetrics & Gynecology, KMC, Manipal University, India, between August 2013 and Aug 2014. A total of 150 subjects that had induced labor or direct caesarean section for various indications and also having low-normal (5-8) / low (<5) AFI, were recruited. Subjects with fetal anomalies were excluded. Outcome variables studied were, fetal distress in labor, thick meconium stained amniotic fluid, mode of delivery in induced labor, perinatal asphyxia, and respiratory distress syndrome. Results: Out of 150 subjects, 68 (45.4%) had low and 82 (54.6%) had low-normal AFI. Both the groups were matched for demographic characteristics and confounding factors for neonatal outcome. In low AFI group the incidence of Low APGAR (11.7%), perinatal asphyxia (11.7%) and RDS (16.1%) were significantly higher compared to those in low-normal group (3.6%, 1.2% and 2.4% respectively) p = 0.057, 0.006 and 0.002. There was no significant difference between the groups with respect to mode of delivery when labor was induced. Conclusions: Low AFI, especially when it is <5, is an indicator of fetal compromise and one may anticipate perinatal asphyxia and RDS. Hence it is prudent to contemplate delivery when the AFI is between 5 and 8.